Safety and efficacy assessment of aerogels for biomedical applications - Ferreira-Gonçalves, Tânia (2022)
The unique physicochemical properties of aerogels have made them an attractive class of materials for biomedical applications such as drug delivery, regenerative medicine, and wound healing. Their low density, high porosity, and ability to regulate the pore structure makes aerogels ideal nano/micro-structures for loading of drugs and active biomolecules. As a result of this, the number of in vitro and in vivo studies on the therapeutic efficacy of these porous materials has increased substantially in recent years and continues to be an area of great interest. However, data about their in vivo performance and safety is limited. Studies have shown that polymer-based, silica-based and some hybrid aerogels are generally regarded as safe but given that studies on the acute, subacute, and chronic toxicity for the majority of aerogel types is missing, more work is still needed. This review presents a comprehensive summary of different biomedical applications of aerogels proposed to date as well as new and innovative applications of aerogels in other areas such as decontamination. We have also reviewed their biological effect on cells and living organisms with a focus on therapeutic efficacy and overall safety (in vivo and in vitro).